PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 021 BUNGA TANJUNG INDRAGIRI HULU - Gunawan Gunawan; Damanhuri Daud; Jesi Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Problem of this research study of IPA in class VB SDN 021 Bunga Tanjung. Still many child which not yet reached KKM. From result of tes in the reaity from 18 student people only 7 people (38,88%) reaching KKM, while 11 student people (61,11%) not reach specified KKM that is (70). As for average value is 65,33. This result strenghtened with the following symptomos among other: Assess result of low student; passive student in learning IPA because model of pembelajar imprecise with items, student feel saturated in learning IPA because not be applied in the world of reality; learn in teaching still using conventional methods; Teacher do not use correct model for the study of IPA. This research to increase result of learning IPA class student of VB SDN Bunga Tanjung school year 2014 / 2015. Research Subject is class student of VB SDN Bunga Tanjung with amount of student 18 student people. Form this research is research of class action with two cycle, with ability and characteristic which is hetrogen. Research data indicate that result learn natural student of improvement, activity provision value learn at cycle of I with mean is 64%. At cycle of II mount with mean 77%. Student activity at cycle of I with 66%. At cycle of II mount with mean 74%. And result of natural research of improvement, where before conducted by study cooperative of Make a Match at complete elementary score 7 people (38,00) with mean65,33. After given action by using model study of type cooperative of Make a Match at cycle of I moun with complete student reach 16 people (88,88%) with mean 87,05. Cycle of II attainment of complete student 16 people (88,88) increase at mean 87,33. Up of result learn in its entirety is 33,67%. Thereby can be concluded that hypothesis in this research is” Applying model study of type Make a Match can improve result learn IPA class student of VB SDN 021 Bunga Tanjung”.Key Word : Model study type cooperative of Make a Match, Result Learn IPA